Ubiquitin-Specific Peptidase 7: A Novel Deubiquitinase That Regulates Protein Homeostasis and Cancers - Zhou, Lin; Ouyang, Taohui; Li, Meihua; Hong, Tao; MHS, Alriashy; Meng, Wei; Zhang, Na (Frontiers in Oncology, 2021)
Ubiquitin-Specific Peptidase 7 (USP7) , or herpes virus-associated protease (HAUSP), is the largest family of the deubiquitinating enzymes (DUBs). Recent studies have proved that USP7 plays a vital role in regulating various physiological and pathological processes. Dysregulation of these processes mediated by USP7 may contribute to many diseases, such as cancers. Moreover, USP7 with aberrant expression levels and abnormal activity are found in cancers. Therefore, given the association between USP7 and cancers, targeting USP7 could be considered as an attractive and potential therapeutic approach in cancer treatment. This review describes the functions of USP7 and the regulatory mechanisms of its expression and activity, aiming to emphasize the necessity of research on USP7, and provide a better understanding of USP7-related biological processes and cancer.